Neoconservatism and the New American Century - Ryan, M. author. aut Link
X, 273 p.
Keywords: Situated at the intersection of political history, intellectual history, and the history of U.S. foreign policy, this book offers an in-depth examination of the development of neoconservative foreign policy from the end of the Cold War to the election of George W. Bush in 2000.